Characterization of the Reduction of Selenate and Tellurite by Nitrate Reductases - Sabaty, Monique (American Society for Microbiology, 2001)
Preliminary studies showed that the periplasmic nitrate reductase (Nap) of Rhodobacter sphaeroides and the membrane-bound nitrate reductases of Escherichia coli are able to reduce selenate and tellurite in vitro with benzyl viologen as an electron donor. In the present study, we found that this is a general feature of denitrifiers. Both the periplasmic and membrane-bound nitrate reductases of Ralstonia eutropha, Paracoccus denitrificans, and Paracoccus pantotrophus can utilize potassium selenate and potassium tellurite as electron acceptors. In order to characterize these reactions, the periplasmic nitrate reductase of R. sphaeroides f. sp. denitrificans IL106 was histidine tagged and purified. The V(max) and K(m) were determined for nitrate, tellurite, and selenate. For nitrate, values of 39 μmol · min(−1) · mg(−1) and 0.12 mM were obtained for V(max) and K(m), respectively, whereas the V(max) values for tellurite and selenate were 40- and 140-fold lower, respectively. These low activities can explain the observation that depletion of the nitrate reductase in R. sphaeroides does not modify the MIC of tellurite for this organism.